Prevalence of sarcopenia in Germany and the corresponding effect of osteoarthritis in females 70 years and older living in the community: results of the FORMoSA study - Kemmler W; Teschler M; Goisser S; Bebenek M; von Stengel S; Bollheimer LC; Sieber CC; Freiberger E (Clinical Interventions in Aging, 2015)
Wolfgang Kemmler,1 Marc Teschler,1 Sabine Goisser,2 Michael Bebenek,1 Simon von Stengel,1 Leo Cornelius Bollheimer,2,3 Cornel C Sieber,2,3 Ellen Freiberger2 1Institute of Medical Physics, University of Erlangen-Nürnberg, Erlangen, Germany; 2Institute for Biomedicine of Aging, University Erlangen-Nürnberg, Nürnberg, Germany; 3Department of General Internal Medicine and Geriatrics, St John of God Hospital, Regensburg, GermanyBackground: Although sarcopenia represents a challenging burden for health care systems around the world, its prevalence in the elderly population varies widely. The primary aim of the study was to determine the prevalence of sarcopenia in community-dwelling (CD) German women aged 70 years and older; the secondary aim was to assess the effect of osteoarthritis (OA) on sarcopenia prevalence in this cohort.Methods: A total of 689 Caucasian females 18–35 years old and 1,325 CD females 70 years+ living in Northern Bavaria, Germany, were assessed during the initial phase of the FORMoSA research project. Anthropometry, total and regional muscle mass, were assessed by segmental multifrequency Bioelectrical Impedance Analysis. Further 10 m walking speed and handgrip strength were evaluated to apply the European Working Group on Sarcopenia in Older People definition of sarcopenia. Covariates were determined by questionnaires and interviews.Results: Applying the algorithm of the European Working Group on Sarcopenia in Older People of two standard deviations below the mean value for appendicular skeletal muscle mass of a reference cohort of the young cohort (5.66 kg/m2), low gait speed (≤0.8 m/s), and low grip strength (<20 kg), the prevalence of sarcopenia in CD German females 70 years and older was 4.5% (70–79 years: 2.8% vs ≥80 years: 9.9%; P<0.001). Participants with OA at the hip and lower limbs (n=252) exhibited significantly higher rates of sarcopenia (OA: 9.1 vs non-OA: 3.5%). Of importance, anthropometric, demographic, health, and lifestyle parameters (except exercise participation) of our cohorts corresponded with Bavarian or German data for CD women 70 years+.Conclusion: The prevalence of sarcopenia in CD German females 70 years+ is relatively low. However, participants with OA at the hip or lower limbs were at increased risk for sarcopenia.Keywords: sarcopenia, prevalence, osteoarthritis, Germany